Urine β2-Microglobulin and Retinol-Binding Protein and Renal Disease Progression in IgA Nephropathy - Shen, Xiaoqi; Cheng, Jun; Yu, Guizhen; Li, Xiayu; Li, Heng; Chen, Jianghua (Frontiers in Medicine, 2021)
Background: Tubulointerstitial involvement has been reported to have a decisive influence on the progression of IgA nephropathy (IgAN). High levels of urine β2-microglobulin (β2-MG) and retinol-binding protein (RBP) were observed in patients with IgAN with tubulointerstitial lesions. However, their roles in disease progression remain unclear. This study aimed to evaluate the associations of urine β2-MG and RBP with the progression of IgAN. Methods: We retrospectively investigated a cohort of 2,153 patients with IgAN. Clinical and pathological features, outcomes, and urine β2-MG, and RBP at the time of biopsy were collected. The associations, of urine β2-MG and RBP with the composite renal outcome, defined as a decline in estimated glomerular filtration rate (eGFR) of ≥50% from baseline or end-stage renal disease (ESRD), were examined using restricted cubic splines and the Cox proportional hazards models. Results: During a median follow-up of 20.40 months, 140 (6.50%) patients reached the composite renal outcomes. Restricted cubic splines showed that patients with higher urinary β2-MG and RBP levels had worse renal outcomes. The Cox regression analysis revealed that urine β2-MG and RBP were associated with a risk of the composite renal outcome in the multivariate adjusted model [+1 SD for log β2-MG, hazard ratio (HR) = 1.462, 95% CI: 1.136–1.882, p = 0.003; +1 SD for log RBP, HR = 1.972, 95% CI: 1.486–2.617, p = 0.001]. The associations were detectable within patients with baseline eGFR <90 ml/min/1.73 m2 (+1 SD for log β2-MG, HR = 1.657, 95% CI: 1.260–2.180, p < 0.001; +1 SD for log RBP, HR = 1.618, 95% CI: 1.199–2.183, p = 0.002), but not among patients with eGFR ≥90 ml/min/1.73 m2. Conclusion: Higher levels of urine β2-MG and RBP were independent risk factors for renal disease progression in IgAN.